Atomic Habits Parenting Validating a Behavioral Framework for Stunting Prevention - Sirajuddin, Sirajuddin; Mustamin, Mustamin; Dien Abdul Munir (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Atomic Habits Parenting focuses on small, consistent actions by caregivers to detect and prevent stunting in children. A valid and reliable instrument is essential for early detection and effective prevention. This study aims to evaluate the validity and reliability of the Atomic Habits Parenting instrument and its association with stunting prevention in children under five. This method differs from others as the consistent daily practice of small habits leads to a 37-fold improvement over one year. Methods: A cross-sectional study was conducted in Jeneponto, Barru, and Sinjai Districts of South Sulawesi, Indonesia, involving 900 children aged 0-59 months. Data were collected from February to August 2024. Validity and reliability were assessed using Cronbach's alpha, sensitivity, and specificity with ROC analysis, and the association with stunting was measured using the Chi-Square test. Results: The instrument demonstrated high reliability with Cronbach's alpha values above 0.8 for all parenting practices. ROC analysis showed excellent sensitivity (75.6%) and specificity (82.3%) at a threshold score of 313.5. A significant association was found between Atomic Habits Parenting and stunting prevention (p<0.001). Conclusion: The Atomic Habits Parenting instrument is valid and reliable, with strong sensitivity and specificity. It is significantly associated with the prevention of stunting in children under five, making it a valuable tool for public health programs. Adapting this approach globally in high-stunting regions (>20%) could support a sustainable stunting reduction roadmap.